Consumers' willingness to pay for biodegradable shopping bags in selected hypermarkets in Selangor, Malaysia - Subahir, Fatimah Az Zaharah (2014)
Malaysia is facing critical pollution and environmental deterioration issues as a result of massive consumption of plastic- since it takes more than 300 years to be disposed. Introduction of biodegradable shopping bag (BSB) as a greener alternative is deemed as the best substitute for plastic bags, due to its disposability nature in order to preserve the environment, thus, preventing environmental distortion or environmental problem. The general objective of this study is to determine the consumer awareness and estimate their willingness to pay for BSB. On the other while, the specific objectives of this study are; i) to determine the consumer awareness towards the environment and biodegradable shopping bag, ii) to determine the dimension of consumer perception towards the usage of biodegradable shopping bag, and iii) to estimate consumer willingness to pay for BSB. Data are obtained through face to face interviews by using closed ended and multiple categories questionnaire. A sample of 300 respondents is randomly chosen at selected hypermarkets in Selangor in September to November 2012. Data are analysed using descriptive analysis, factor analysis and Contingent Valuation Method (CVM). Four factors that significantly influence consumers to use BSB are found through the factor analyses, namely; behaviour and lifestyle concern, environmental concern, knowledge of BSB and negative attributions toward environment. The results obtained from the analysis indicate that price of BID, AGE, GENDER (MALE) and INCOME are significant in influencing the consumers‟ willingness to pay for BSB. The result of the survey also reveals that consumers are willing to pay an additional premium of RM 3.53 per unit of BSB. In this regards, findings from this study are believed to provide some guidance for the policy makers and business operators to revise the BSB price introduced to consumers. Increase in consumers‟ demand for BSB and their environmental awareness may lead to subsequent reduction or elimination of the plastic shopping bags usage, and ultimately make our environment healthier by reducing environmental degradations and distortions.